THE EFFECT OF EASE OF TRANSACTIONS AND PROMOTIONS ON PURCHASING DECISIONS USING GOPAY E-MONEY PAYMENTS IN THE NEW NORMAL ERA (STUDY CASE ON DEAR BUTTER AT MALL PODOMORO MEDAN) - Siaufanti, stella (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This research was conducted with the aim of determining the effect of Ease of Transaction and Product Promotion on Purchasing Decisions using Gopay E-Money Payments in the New Normal era on Dear Butter at Podomoro Mall Medan. The research method used is quantitative descriptive survey research. The study used data collection techniques in the form of questionnaires. The population in this study was all customers who shopped at Dear Butter Mall Podomoro Medan with an uncertain amount. Using the Slovin Formula, the number of Customers Per ordinary day and weekend is multiplied by 4 weeks and multiplied by 2 months so that 720 respondents are obtained. Multiple linear regression research tests are used as an analytical tool to find out how the influence between independent and dependent variables is. This study also aims to help digital wallet companies in Indonesia, especially Gopay, by providing input for companies to determine the right steps to improve the factors that influence purchasing decisions. The results of this study show that both partially and simultaneously the variable Ease of Transaction and Promotion has a significant effect on Purchasing Decisions using E-Money Gopay in the New Normal era at Dear Butter Mall Podomoro Medan Variables of Convenience and Promotion are able to explain the variations that occur in Purchasing Decisions Using Gopay E-Money in the New Normal era at Dear Butter Mall Podomoro as much as 50%.